The development of a step-down switched-capacitor inverter without flying capacitors and full-bridge circuits - Kei Eguchi; Hiroto Abe; Takaaki Ishibashi; Farzin Asadi (Energy Reports, 2020)
Recently, an inductor-less inverter attracts many researchers' attention, because the inductor-less design can provide not only small size but also small electromagnetic interference (EMI). In this paper, we propose a novel step-down switched-capacitor (SC) inverter without flying capacitors. Unlike traditional single-phase inverters, the proposed single-phase inverter has the advantages, namely, inductor-less design, downsizing by omitting flying capacitors, no full-bridge circuit, and symmetrical topology. To achieve these features, the proposed SC inverter changes the connection order of series-connected capacitors alternately. By offering a simple circuit configuration, the proposed inverter can achieve not only small EMI but also small size and high power efficiency. Furthermore, by using pulse width modulation (PWM), the proposed inverter generates a sinusoidal output without flying capacitors and full-bridge circuits. The effectiveness of the proposed inverter is justified by comparing the proposed inverter with an existing single-phase SC inverter. The simulation program with integrated circuit emphasis (SPICE) simulations demonstrate that the proposed inverter outperforms the existing SC inverter in the points of power efficiency and component counts. Concretely, about 94% power efficiency can be achieved when the output power is 2kW. Furthermore, the proposed inverter can reduce two flying capacitors from the existing SC inverter.
Keywords: 330; Inductor-less inverters; No full-bridge inverters; Step-down inverters; Switched-capacitor techniques; Symmetrical topology